Total synthesis of (+/-)/(+)-subincanadine E and determination of absolute configuration - Kalshetti, Manojkumar G.; N. P. Argade (Journal of Organic Chemistry, 2017)
A facile synthesis of (+/-)-subincanadine E was described from tryptamine-based maleimide. 1,2-Addition of Grignard reagent to maleimide, internal activation of formed lactamol for in situ 1,4-addition of Grignard reagent, and associated position-specific allylic rearrangement in diastereoselective Pictet-Spengler cyclization were the key steps. Enantioselective first total synthesis of naturally occurring cytotoxic (+)-subincanadine E was also accomplished from (S)-acetoxysuccinimide via an unusual syn-addition of cuprate to the alpha/beta-unsaturated lactam. Sinister absolute configuration was assigned to (+)-subincanadine E on the basis of total synthesis. (S)-Acetoxy group in the succinimide precursor was initially employed to impart regio- and stereoselectivity and then as a suitable leaving group to generate the desired conjugated lactam.